2006
DOI: 10.1016/j.rmed.2006.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic nervous system control of the cardiovascular and respiratory systems in asthma

Abstract: Patients with asthma have exaggerated bronchoconstriction of their airways in response to certain indirect (e.g. cold air, allergens, dust, exercise) or direct (e.g. inhaled methacholine) stimuli. This 'hyper-reactivity' usually co-exists with airway inflammation, although the pathophysiological mechanisms underlying these changes are not fully understood. It is likely that this hyper-reactivity is associated with abnormal autonomic nervous system (ANS) control. In particular, the parasympathetic (vagal) compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(84 citation statements)
references
References 127 publications
3
75
0
6
Order By: Relevance
“…Methacholine is known to produce bronchoconstriction of the airways [57], which is thought to be driven by parasympathetic activation [58,59]. Methacholine has also been shown to lower blood pressure [60], so it is plausible that a methacholine-induced imbalance between parasympathetic and sympathetic tone could explain our results of diminished physiological responses in reaction to the MCT.…”
Section: Discussionmentioning
confidence: 76%
“…Methacholine is known to produce bronchoconstriction of the airways [57], which is thought to be driven by parasympathetic activation [58,59]. Methacholine has also been shown to lower blood pressure [60], so it is plausible that a methacholine-induced imbalance between parasympathetic and sympathetic tone could explain our results of diminished physiological responses in reaction to the MCT.…”
Section: Discussionmentioning
confidence: 76%
“…Such an effect could contribute to airway hyperreactivity such as occurs in asthma. 62 We found that VIP and SP, but not NGF or CGRP, caused human mast cells to produce chemokines such as RANTES and MCP-1, suggesting that these mediators may be involved in neurogenic inflammation. Injections of RANTES in the skin of humans and of rats caused eosinophil and macrophage recruitment.…”
Section: Discussionmentioning
confidence: 69%
“…A reflex response occurs when there is a change in the blood pressure or the chemistry within the body. This makes the cardiovascular centre to stimulate or inhibit the cardioacceleratory centre, the cardioinhibitory centre and the vasomotor centre until equilibrium or homeostasis is reached [10] (Figure 3). …”
Section: Cardiovascular Controlmentioning
confidence: 99%